Research on the Factors Affecting the Total Factor Productivity of Chinese Life Insurance Companies - Sun, Zhe (Archives of Business Research, 2020)
Based on the latest method of total factor productivity research at home and abroad, this paper uses the panel data of 17 Chinese life insurance companies from 2007 to 2016 to estimate the total factor productivity of Chinese insurance companies using the Malmquist index analysis method of DEA model. The measurement method is a regression analysis of several factors affecting the total factor productivity of Chinese insurance companies. The empirical results show that among the micro factors, the asset-liability ratio, asset turnover, operating efficiency and company size have a significant impact on the total factor growth rate of Chinese life insurance companies. Among the macro factors, GDP growth rate, inflation rate and unemployment rate have a significant impact on the total factor growth rate of Chinese life insurance companies.